A New Approach for Provenance Studies of Archaeological Finds: Inferences from Trace Elements in Carbonate Minerals of Alpine White Marbles by a Bench-to-Top μ-XRF Spectrometer. (6th February 2014) - Vaggelli, Gloria; Serra, Margherita; Cossio, Roberto; Borghi, Alessandro
Abstract : The metamorphic rocks outcropping in the Western Alps are characterised by a great variety of white marbles which have been used since the antiquity. This variety mostly includes nine historical Piedmont white marbles (Ornavasso, Candoglia, Crevola, Pont Canavese, Foresto, Chianocco, Prali, Brossasco, and Garessio marbles) coming from well-known quarry sites and belonging to different metamorphic geological units of the Western Alps. The petrographical, minerochemical, and C–O isotopic data of these white marbles have been integrated with CaO and trace element (Fe, Mn, and Sr) concentration determined on single crystals of carbonate minerals (i.e., calcite and/or dolomite) by means of a bench-to-top µ-XRF spectrometer. Principal component analysis and hierarchical cluster analysis were performed on a data set of 178 observations containing CaO, Fe, Mn, and Sr concentration as well as the maximum grain size (MGS), δ 18 O and δ 13 C. The use of only five selected variables (CaO, Fe, Mn, Sr, and δ 18 O) has provided the correct allocation of each individual observation to its relevant class. Therefore, this approach based mostly on a noninvasive µ-XRF determination will be useful to define the provenance of unknown marbles of alpine origin used in antiquity for cultural heritage.